Without an educational project there is no education (Journal of Parents and Teachers, 2025)
Companies and many organisations and associations are entering into a new organisational system, which the world of education must also consequently incorporate. Hence the need to create an educational project, which is the main management tool for a school. This involves designing a specific model to be applied by teachers to a group of students over a certain period of time. The Educational Project will help to harmonise diversity through the organisation and participation of everyone, guided by and tailored to the needs of the students.
Keywords: educational project, organisation, participation, planning, harmonisation